PHILOSOPHY OF SECURITY UNDER MARTIAL LAW - OLEKSIUK, Myron; GAIVORONIUK, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the problems of security philosophy and the peculiarities of its implementation in the conditions of martial law and real challenges to the existence of the Ukrainian state and its citizens. The philosophy of security considers the latter as a phenomenon of an objective order that exists in an uncivilized space, functions independently of a certain historically formed society, but is always ensured by the active participation of a person in security processes.Under martial law, security philosophy is a conceptual approach that combines two important components. On the one hand, it is based on the organization of the state and society, which pays the most attention to economic security issues, because it is in this area that conditions are created for the maximum mobilization of material resources in order to resist hostile actions. But, on the other hand, it keeps in focus the person who is the main value of a democratic state, his life and security.Its financial, social, and information components continue to be important aspects of security philosophy. Special emphasis in the security philosophy is placed on the factor of information warfare imposed by the aggressor state with the aim of value deformation of the consciousness of Ukrainian citizens, undermining the national-patriotic spirit of Ukrainian citizens, depersonalization of individual responsibility before the threat of loss of statehood and national identity. This is precisely why we highlight another aspect of the security philosophy - the valuable one.The problems of the implementation of state security in the conditions of the introduction of martial law are considered in the article as particularly important and vitally necessary, as they concern both the very existence of the state and its citizens, taking into account the actions of the enemy, which carry a kind of genocide of the Ukrainian people.
Keywords: security; martial law; socil security; economic security; financial security; information security